2018
DOI: 10.3389/fpls.2018.00679
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Crystal Morphology of Epicuticular Wax in Mature Fruits of 35 Pear (Pyrus spp.) Cultivars

Abstract: An evaluation of fruit wax components will provide us with valuable information for pear breeding and enhancing fruit quality. Here, we dissected the epicuticular wax concentration, composition and structure of mature fruits from 35 pear cultivars belonging to five different species and hybrid interspecies. A total of 146 epicuticular wax compounds were detected, and the wax composition and concentration varied dramatically among species, with the highest level of 1.53 mg/cm2 in Pyrus communis and the lowest l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 51 publications
5
26
1
Order By: Relevance
“…An inverse relationship between triterpenoid acids and olive fly egg deposition has been reported elsewhere (Kombargi et al, 1998). Triterpenoids also have reportedly an important role in the mechanical strength of fruit cuticles (Tsubaki et al, 2013; Wu et al, 2018), and have been shown to be related to weight loss and softening rates in blueberry (Moggia et al, 2016). In this work, however, no such relationship was observed between the incidence of olive fly infestation and triterpene content ( Table 4 , Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…An inverse relationship between triterpenoid acids and olive fly egg deposition has been reported elsewhere (Kombargi et al, 1998). Triterpenoids also have reportedly an important role in the mechanical strength of fruit cuticles (Tsubaki et al, 2013; Wu et al, 2018), and have been shown to be related to weight loss and softening rates in blueberry (Moggia et al, 2016). In this work, however, no such relationship was observed between the incidence of olive fly infestation and triterpene content ( Table 4 , Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from alkanes and triterpenoids, many fruits have high proportions of other components in their cuticles. A recent study indicated high levels of primary alcohols and tocopherols in the cuticular wax of some pear cultivars (Wu et al, 2017, 2018). Plum ( Prunus domestica ) and some apple cultivars show high proportion of secondary alcohols in fruit cuticle, while tomato cuticle contains significant amounts of polyunsaturated constituents, including alken-1-ols and alkenes (Kosma et al, 2010).…”
Section: Cuticular Wax Composition and Biosynthesis In Fruitsmentioning
confidence: 99%
“…lAAld can be oxidezed to the auxin indole-3-acetic acid (IAA) and is related to the tryptophan metabolim (Tsurusaki et al, 1997). Octadecanal is a lipid, found in the cuticular wax of maize (Perera and Nicolau, 2007) and epicular wax of pear fruits (Wu et al, 2018). All metabolites were negatively correlated with two chloroplastic proteins: translocase and a protease.…”
Section: Discussionmentioning
confidence: 99%